Poly(ester-acrylate/amine) Dendrimers - Tomalia, Donald A.; Rookmaker, Margaret (Polymer Data Handbook, 2009)
Structure Dendrimers are three-dimensional macromolecules consisting of three major architectural components: a core, branch cells, and terminal groups. These products are constructed from repeat units called branch cells